Segunda Guerra, pracinhas e impressos : um estudo sobre o jornal O Cruzeiro do Sul (1945) - Reis, Dercio Cardoso (2019)
This research has carried out a study upon the newspaper “O Cruzeiro do Sul”, which was produced by the Special Service of the Brazilian Expeditionary Force. It was a regular publication, edited twice a week, manufactured between January the 3rd and May the 31st of the year 1945, adding up to 34 editions. Nevertheless, its circulation throughout all of Italy had become restricted. It was the main printed paper that helped Brazilian soldiers form their opinion about World War II. The newspaper was printed in Florença and had a print run of about 5,000 copies. By studying this newspaper, we attempt to analyze the representation made by O Cruzeiro do Sul, giving precedence to the proposal of the newspaper in order to educate with images and texts the soldiers of the BEF, to how Brazil was represented and to the reasons for the Brazilian presence at the World War II battles. We see the newspaper as an educational source. We observe an educational process, but not scholastic. For a better understanding it is indispensable to take into consideration that the newspaper is a mere news transmitter. It is necessary to understand the typology of the newspaper, which is its objective, to what kind of reader it had been addressed, thus facilitating a better understanding and, likewise, a future criticism.